Computer‐Mediated Communication in Intimate Relationships: Associations of Boundary Crossing, Intrusion, Relationship Satisfaction, and Partner Responsiveness. (15th June 2017) - Norton, Aaron M.; Baptist, Joyce; Hogan, Bernie
Abstract : This study examined the impact of technology on couples in committed relationships through the lens of the couple and technology framework. Specifically, we used data from 6, 756 European couples to examine associations between online boundary crossing, online intrusion, relationship satisfaction, and partner responsiveness. The results suggest that participants' reports of online boundary crossing were linked with lower relationship satisfaction and partner responsiveness. Also, lower relationship satisfaction and partner responsiveness were associated with increased online boundary crossing. The results suggest that men, but not women, who reported greater acceptability for online boundary crossing were more likely to have partners who reported lower relationship satisfaction in their relationships. Implications for clinicians, relationship educators, and researchers are discussed. Abstract : Video Abstract is found in the online version of the article.